The Effect of Eco-efficiency and Environmental Performance on Company Value with Company Size as a Moderating Variable: Array - Muhammad Syahrizam; Yunita Fitria (JASS (Journal of Accounting for Sustainable Society), 2025)
This study aims to analyze the effect of eco-efficiency and environmental performance on firm value, with company size moderating the relationship between Eco-efficiency and environmental performance on firm value. The population in this study are manufacturing companies listed on the Indonesia stock exchange for the period 2021 - 2023. The sampling technique used purposive sampling method. purposive sampling and obtained 45 companies that met the criteria. The type of data used is secondary data and the hypothesis testing method uses multiple regression analysis with the Moderate Regression Analysis (MRA) technique. Based on the results of this study, it shows that the variable eco-efficiency and environmental performance has a significant positive effect on firm value. With the moderation variable used, namely company size, it shows that company size has a significant positive effect on the relationship between eco-efficiency variables and environmental performance on firm value.